Rekonstruksi Kalimat pada Teks Berita di Laman CNN Indonesia Edisi Desember 2023 sebagai Bahan Ajar Membaca Kritis Siswa Kelas 12 SMA - Nabila Dila Ardiyanti; Ahmad Ma’arijul Amri; Yulian Akbar Rizki Nur Fazri; Ika Apriliani; Alifia Khoirun Nisa; Asep Purwo Yudi Utomo; Uki Hares Yulianti (Universitas Palan, 2024)
News is a text that has an important role in disseminating information. News text is so useful that it has become a literacy material for students due to the development of advanced technology. Although it has become one of the sources of student literacy, online news texts are still classified as having syntactic errors such as a lack of understanding of the language used in compiling a sentence in the news. The purpose of this study is to describe sentence errors in the news contained in the old CNN Indonesia news, such as